Effects of Partial Sleep Deprivation on Proinflammatory Cytokines, Growth Hormone, and Steroid Hormone Concentrations During Repeated Brief Sprint Interval Exercise. (May 2013) - Abedelmalek, Salma; Souissi, Nizar; Chtourou, Hamdi; Denguezli, Meriam; Aouichaoui, Chirine; Ajina, Monia; Aloui, Asma; Dogui, Mohamed; Haddouk, Samy; Tabka, Zouhair
<x xml:space="preserve">Abstract</x> The purpose of this study was to evaluate the effects of partial sleep deprivation (PSD) on circulating concentrations of interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) in relation to the secretory profiles of growth hormone (GH), cortisol, and testosterone during a repeated brief sprint interval exercise. Thirty healthy football players (mean age: 21.1 [range: 18–24] years; body mass index [BMI]: 22.6 [range: 18.47–24.46] Kg/m2) completed two test sessions at 08:00 h, one scheduled after a baseline night (bedtime: from 22:30 to 07:00 h) and the other after a PSD night caused by an early awakening (bedtime: from 22:30 to 03:00 h). During each session, participants performed 4 × 250-m run on a treadmill at a constant intensity of 80% of the personal maximal speed with a 3-min recovery in between. Tests session were performed at 08:00 h. Blood samples were collected before, immediately after the first and the fourth 250-m run, and 60 min after the exercise. The results showed that cortisol concentrations were not affected by the PSD. However, GH and testosterone concentrations were higher (p < .05) 60 min after the exercise during PSD in comparison with baseline. Likewise, plasma concentrations of IL-6 and TNF-α were higher (p < .05) after PSD during the exercise (i.e., the first and the fourth run) and remained elevated during the recovery period (i.e., 60 min after the exercise). In conclusion, these results showed that sleep restriction increases the proinflammatory cytokine, GH, and testosterone concentrations after physical exercise but did not affect the cortisol responses. (Author correspondence: n_souissi@yahoo.fr)